Funkcje nazw własnych w Fimfárum Jana Wericha - WOŹNIAK, Paulina (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2009)
Artykuł porusza problematykę funkcji nazw własnych w tekście literackim. Przedmiotem badania jest zbiór bajek Jana Wericha pt. Fimfárum. Na bogatym materiale ezgemplifikacyjnym zostało omówionych siedem funkcji nazw własnych: lokalizacyjna w przestrzeni (toponimy, choronimy, urbonimy, ergonimy), lokalizacyjna w czasie (choronimy, mitonimy, nazwy wydarzeń historycznych, nazwy mieszkańców państw), socjologiczna (imiona i ich ekwiwalenty, nazwiska, nazwy mieszkańców państw, etnonimy, faleronimy), treściowa (imiona i ich ekwiwalenty, nazwiska, przezwiska, ojkonimy, mitonimy, ideonimy), ekspresywna (neologizmy w nazwach pojedynczych egzemplarzy i roślin), informacyjna (ergonimy, porejonimy, mitonimy, heortonimy, nazwy napojów), aluzyjna (heortonimy, motionimy, chrematonimy).

The article raises the issue of the function of proper names in the literary text. The subject of the research is a collection of Jan Werich’s fairy tales entitled Fimfárum. On the basis of rich exemplification material there were discussed seven functions of proper names: location in space (toponyms, choronyms, urbonyms, ergonyms), location in time (choronyms, metonyms, names of historical events, names of inhabitants of countries), sociological function (first names and their equivalents, surnames, names of inhabitants of countries, ethnonyms, faleronyms), content function (first names and their equivalents, surnames, nicknames, oiconyms, metonyms, ideonyms), expressive function (neologisms in names of single specimens of plants), informative function (ergonyms, porejonyms, metonyms, heortonyms, names of drinks), allusive function (heortonyms, motionyms, chrematonyms).
Function of proper names in the Fimfárum by Jan Werich
Keywords: Język czeski; Czech language; Dzieło literackie; Literary work; Przekład; Translation; Onomastyka; Onomastic; Nazwy własne; Proper names